Bimodal Probe for Magnetic Resonance Imaging and Photoacoustic Imaging Based on a PCTA‐Derived Gadolinium(III) Complex and ZW800–1. Issue 29 (10th July 2019) - Devreux, Marie; Henoumont, Céline; Dioury, Fabienne; Stanicki, Dimitri; Boutry, Sébastien; Larbanoix, Lionel; Ferroud, Clotilde; Muller, Robert N.; Laurent, Sophie
Abstract : One of the most widely used techniques to obtain anatomical information is magnetic resonance imaging (MRI). Despite its high resolution, it has a low sensitivity which could be enhanced by coupling MRI with a more sensitive technique such as photoacoustic imaging (PAI). The development of a bimodal agent could thus lead to hybrid images with a high anatomical resolution provided by MRI and a precise localization of the contrast agent thanks to PAI. The probes used in this work are a gadolinium(III) complex derived from PCTA‐[12] for MRI and the ZW800–1 fluorophore for PAI. These two organic parts have been attached to a L ‐lysine derivative which has a third site for potential conjugation to a biovector, thus opening the field of targeted probes for molecular imaging. Preliminary relaxometric and photoacoustic characterizations indicate that this bimodal agent is a promising compound for bimodal imaging. Abstract : Magnetic resonance imaging (MRI) has a low sensitivity. Coupling it with a more sensitive technique like photoacoustic imaging (PAI) improves the quality of the image. The probes explored in this paper are Gd‐PCTA for MRI coupled with ZW800–1 for PAI.